(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Talash I. O. Activization of cognitive activity of future primary school teachers. In article attempt to define a way of activization of cognitive activity of students of psychological and pedagogical faculty in the course of introduction of modular and rating technology of training is carried out.